A Textual Analysis On Portrayal Of Women Characters - Exclusive Focus In Mani Ratnam Movies - et. al., Ms.M.Subhiksha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With an audience of over 70 million, The Tamil cinema industry or popularly known as Kollywood is the second largest movie maker in India behind Bollywood. Despite catering to such a large audience, Tamil movies have a bad reputation for its over the top - over dramatic - logic lacking masala movies, Hero worship, plagiarism, objectification of women etc. Known for its male dominated characters, Tamil movies are known to depict the feminine character just for amusement serving no real purpose to the plot of the film. The popular Indian filmmaker Mani Ratnam has been a exception in this regard though. The general consensus on the the movie making style of Mani Ratnam is that he is someone that has managed to redefine the method of story telling in Tamil cinema and is also known for the portrayal of strong women characters in his movies. The primary aim of this study is to shed light on the depiction of women characters from some of the movies of Mani Ratnam using textual analysis techniques.